2014
DOI: 10.1371/journal.pone.0098711
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Omeprazole and Lansoprazole Enantiomers on Aryl Hydrocarbon Receptor in Human Hepatocytes and Cell Lines

Abstract: Proton pump inhibitors omeprazole and lansoprazole contain chiral sulfur atom and they are administered as a racemate, i.e. equimolar mixture of S- and R-enantiomers. The enantiopure drugs esomeprazole and dexlansoprazole have been developed and introduced to clinical practice due to their improved clinical and therapeutic properties. Since omeprazole and lansoprazole are activators of aryl hydrocarbon receptor (AhR) and inducers of CYP1A genes, we examined their enantiospecific effects on AhR-CYP1A pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…Moreover, we have shown that OM is a potent inducer of HO-1 enzyme, when we compared against DMSO-treated cells. The concentration of OM used in this study was comparable to those used in previous studies (Jin et al , 2014; Novotna et al , 2014). More importantly, we included the blood concentrations that are observed in humans following OM therapy (Cederberg et al , 1992).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, we have shown that OM is a potent inducer of HO-1 enzyme, when we compared against DMSO-treated cells. The concentration of OM used in this study was comparable to those used in previous studies (Jin et al , 2014; Novotna et al , 2014). More importantly, we included the blood concentrations that are observed in humans following OM therapy (Cederberg et al , 1992).…”
Section: Discussionsupporting
confidence: 82%
“…Prior to the gene reporter assays, cytotoxicity of tested compounds in LS174T cells after 24 h of incubation was assessed by conventional MTT test (cytotoxicity of OME and LAN in HepG2 cells and human hepatocytes was tested elsewhere [7]). We did not observe significant decline in viability of LS174T cells by LAN (up to 100 µM) and OME (up to 250 µM) (Figure 3; upper panels).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly the AhR agonistic activity of both 35 and 36 does not conform to the same enantiomeric pattern as noted with their PPI activity. This activity differentiation is attributed to enantiomeric effects of the stereoisomers on AhR activation and CYP1A induction . With these benzimidazoles, the S‐enantiomers displayed stronger AhR activation and CYP1A induction at lower concentrations (1‐10 μM for lansoprazole ( 36 ) and 10‐100 μM for omeprazole ( 35 )), while the R‐enantiomers maintained better activity at higher concentrations (100 μM for lansoprazole ( 36 ) and 250 μM for omeprazole ( 35 )).…”
Section: Exogenous Ligandsmentioning
confidence: 99%